Optic neuritis: relation between inflammatory genetic markers and occurrence of the disease - Punytė , V.; Liutkevičienė , R. (Neurologijos seminarai, 2019)
Optic neuritis (ON) is characterized as an inflammation of the optic nerve. Based on etiology, ON is classified to typical and atypical forms. Typical ON is often related to multiple sclerosis while atypical ON can be caused by various infections, autoimmune disorders or different inflammatory diseases. Although the cause of ON is multifactorial, a lot of attention is given to inflammatory and immune processes which are considered to contribute to demyelination of axons. Typical ON occurs as subacute unilateral decrease in visual acuity (VA) and pain which intensifies during eye movement. Atypical ON is characterized by intense pain or no pain, bilateral decrease in VA, hemorrhages and exudate in optic discs. In typical ON, fast and significant recovery of VA is common while in atypical ON, the prognosis of VA recovery is poor. Thanks to recent advances in the field of genetics, it is possible to identify an increasing number of genes that could be associated with ON pathogenesis.In this article we briefly review the epidemiology, causes, pathophysiology, symptoms, diagnostics and treatment of ON as well as its relation to multiple sclerosis.
Keywords: optic neuritis; symptoms; diagnostics; treatment; multiple sclerosis; IL-6; VEGFA; TIMP-3